When to Refer Patients for Catheter‐based Coronary Angiography (CBCA) - Richard Conti, C. (Clin Cardiol, 2010)
In 2009, much was written about computed tomography (CT) angiography of the coronary circulation and little about catheter‐based coronary angiography, despite its continued use since 1958 in patients with all types of cardiac disease or potential disease. Copyright © 2010 Wiley Periodicals, Inc.